Gay domestic tourists’ motivation: The case of Bali - Roozbeh Babolian Hendijani (Tourism & Management Studies)
Building upon existing literature on gay tourism, gay tourist motivation, and homosexuality, this article explores the primary determinants of motivation to travel for gay tourists in a conservative market and their satisfaction with Bali, an Asian and peripheral destination. The study aims to provide valuable insights for destination marketers and stakeholders in Indonesia, enabling them to develop improved marketing strategies tailored to this niche tourism market. A quantitative approach was employed, utilizing self-administered questionnaires distributed among gay tourists in Jakarta, Indonesia. Descriptive and multiple linear regression analyses were conducted to analyze the experiences of 150 gay domestic tourists in Bali, Indonesia, as a tourist destination. The findings identified escape, experience, and peace as significant factors influencing gay tourists' satisfaction, while friendliness, venue, beach, nightlife, and natural beauty were identified as destination attributes impacting holiday satisfaction. These findings contribute to the existing body of literature on gay tourism, particularly within the Asian context, and provide valuable insights for destination managers and marketers seeking a deeper understanding of this niche market segment.